Comparing the Effectiveness of Endoscopic Surgeries With Intensity-Modulated Radiotherapy for Recurrent rT3 and rT4 Nasopharyngeal Carcinoma: A Meta-Analysis - Peng, Zhouying; Wang, Yumin; Wang, Yaxuan; Fan, Ruohao; Gao, Kelei; Zhang, Hua; Jiang, Weihong (Frontiers in Oncology, 2021)
Background This meta-analysis aimed to compare the efficacy of intensity-modulated radiotherapy (IMRT) and endoscopic surgery (ES) for high T-stage recurrent nasopharyngeal carcinoma (NPC). Methods Relevant studies were retrieved in six databases from 02/28,2011 to 02/28,2021. The 2-year, 3-year, 5-year overall survival (OS) rates and 2-year disease-free survival (DFS) rates were calculated to compare the survival outcomes of the two treatments of IMRT and ES. Combined odds ratios (ORs) and 95% confidence interval (C Is) were measured as effect size on the association between high T-stage and 5-year OS rates. Results A total of 23 publications involving 2,578 patients with recurrent NPC were included in this study. Of these, 1611 patients with recurrent rT3-4 NPC were treated with ES and IMRT in 358 and 1,253 patients, respectively. The combined 2-year OS and 5-year OS rates for the two treatments were summarized separately, and the 2-year OS and 5-year OS rate for ES were 64% and 52%, respectively. The 2-year OS and 5-year OS rate for IMRT were 65% and 31%, respectively. The combined 2-year DFS rates of IMRT and ES were 60% and 50%, respectively. Combined ORs and 95% confidence intervals for 5-year survival suggest that ES may improve survival in recurrent NPC with rT3-4. In terms of complications, ES in the treatment of high T-stage recurrent NPC is potentially associated with fewer complications. Conclusions The results of our study suggest that ES for rT3-4 may be a better treatment than IMRT, but the conclusion still needs to be sought by designing more studies.